Authoritative discourse in a locally-published ELT textbook in Thailand - Jindapitak, Naratip; Boonsuk, Yusop (Indonesian Journal of Applied Linguistics, 2018)
This study examines cultural contents in a locally-published English language teaching (ELT) textbook for primary 6 students in Thailand. It aims to investigate whether the locally-published textbook depicts sources and themes of cultures in a way that perpetuate and reproduce dominant ideologies and how cultural contents in the locally-published textbook were dealt with by an English teacher in the classroom. Grounded on Bakhtin’s notions of authoritative discourse and internally persuasive discourse, the findings revealed that there were mismatches between the cultural representation in the textbook and students’ lived experiences. Concerning how cultural contents were represented in the classroom, there was no evidence that the teacher assisted learners to forge effective linkages between authoritative discourse and their everyday life. The findings are discussed regarding how cultural contents are ideologically depicted in the textbook and how the cultural contents adversely affect students’ learning experience. Implications and recommendations for textbook authors, language teachers, and future research are presented.